Composite heat preservation hard felt and preparation method thereof

By attaching carbon-carbon composite sheets to the surface of the carbon fiber felt and forming a cross-linked network using silicon-modified phenolic resin and other components, the problem of traditional carbon fiber thermal insulation felt being easily eroded by high-temperature steam in ultra-high temperature environments is solved, achieving higher stability and service life.

CN119263866AActive Publication Date: 2025-01-07FOSHAN SHIJIN TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411602093.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Traditional carbon fiber thermal insulation felt is susceptible to erosion by high-temperature steam in ultra-high temperature environments, resulting in uneven local temperature control, reduced insulation performance, and shortened lifespan.

Method used

Carbon-carbon composite sheets are combined with carbon fiber felt. The carbon-carbon composite sheets are attached to the surface of the carbon fiber felt using an adhesive. A stable cross-linked network is formed using silicon-modified phenolic resin, graphite powder, and silicon carbide, which enhances the bonding strength and structural stability.

Benefits of technology

It improves the stability and service life of thermal insulation felt at ultra-high temperatures, resists high-temperature steam erosion, and maintains good thermal insulation performance and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263866A_ABST
    Figure CN119263866A_ABST
Patent Text Reader

Abstract

The invention discloses a composite heat preservation hard felt and a preparation method thereof, and belongs to the field of heat preservation materials. The composite heat-preservation hard felt comprises a carbon fiber felt body and a carbon-carbon composite sheet, the carbon-carbon composite sheet is attached to the surface of the carbon fiber felt body through a binder, and the binder is prepared from the following components in percentage by weight: 20-25% of furan resin, 20-25% of a binder, 10-20% of a binder, 10-20% of a binder and the balance of a filler. 5-8% of silicon modified phenolic resin; 5-8% of graphite powder; 15-20% of carbon powder; 1-2% of silicon carbide powder; 2-3% of a dispersant; 1-2% of a carbonization auxiliary agent; and the balance of solvent. The heat-preservation hard felt has the effect of improving the long-term heat-preservation effectiveness of the heat-preservation hard felt in an ultra-high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermal insulation materials, and in particular to a composite thermal insulation hard felt and a preparation method thereof. Background Art

[0002] The temperature of the silicon carbide crystal pulling thermal environment can reach over 2300℃, so the insulation materials used are of great significance. Insulation materials can not only ensure the safety and reliability of equipment operation, but also significantly improve production efficiency and reduce costs. Currently, commonly used insulation materials mainly include traditional carbon fiber insulation felts. Carbon fiber insulation felts are generally made through special process combination, curing, shaping, carbonization, high temperature treatment and other steps. Carbon fiber insulation felts are widely used due to their good thermal insulation properties, thereby reducing heat energy loss and reducing operating power.

[0003] However, when used for a long time in an ultra-high temperature environment, traditional carbon fiber thermal insulation felt is easily eroded by high-temperature steam in the hot field, causing damage to the carbon fiber thermal insulation felt, resulting in uneven local temperature control in the hot field and reduced thermal insulation effect, and shortening the life of the thermal insulation felt. Summary of the invention

[0004] In order to improve the long-term effectiveness of thermal insulation of thermal insulation hard felt in ultra-high temperature environment, the present application provides a composite thermal insulation hard felt and a preparation method thereof.

[0005] In the first aspect, the present application provides a composite thermal insulation hard felt adopting the following technical solution: A composite thermal insulation hard felt comprises a carbon fiber felt body and a carbon-carbon composite sheet, wherein the carbon-carbon composite sheet is attached to the surface of the carbon fiber felt body by an adhesive, and the adhesive is made of the following components in percentage by weight: Furan resin 20-25%; Silicon modified phenolic resin 5-8%; Graphite powder 5-8%; Carbon powder 15-20%; Silicon carbide powder 1-2%; Dispersant 2-3%; Carbonization aid 1-2%; The balance is solvent.

[0006] By adopting the above technical solution, the carbon-carbon composite sheet is a thin sheet formed of a carbon-carbon composite material. Since carbon atoms have extremely strong affinity with each other, it has good stability, can resist the erosion of high-temperature steam in the silicon carbide thermal field, and protect the carbon fiber felt.

[0007] The binder enables the carbon-carbon composite sheet to have a high bond with the carbon fiber felt body, and is not easy to separate under high temperature conditions. Silicon-modified phenolic resin introduces silicone to produce good high temperature resistance, allowing the phenolic resin and furan resin to form a stable cross-linked network. Graphite powder, carbon powder and silicon carbide are doped in the cross-linked network to play a role in filling and lubricating dispersion, strengthening the bonding force of the binder on the carbon-carbon composite sheet and the carbon fiber felt body, while resisting the erosion of high-temperature steam, further improving the overall structural stability of the thermal insulation hard felt, so that the thermal insulation hard felt can still be stable for a long time under ultra-high temperatures, and improving the overall service life of the thermal insulation hard felt.

[0008] Optionally, the carbon-carbon composite sheet is made of carbon fiber solidified with resin, with a thickness of 3±1 mm and a density of 1.5-1.8 g / cm 3 .

[0009] By adopting the above technical solution, the carbon-carbon composite sheet has high density, strong barrier ability to high-temperature gases, and high corrosion resistance.

[0010] Optionally, the silicon-modified phenolic resin is a long-chain silane coupling agent modified phenolic resin, wherein the long-chain silane coupling agent is formed by reacting a long-chain acid ester with an aminosilane coupling agent, and the long-chain silane coupling agent is added during the synthesis of the phenolic resin to obtain the long-chain silane coupling agent modified phenolic resin.

[0011] By adopting the above technical scheme, the long-chain silane coupling agent introduces silicone into the phenolic resin while also introducing the aliphatic long carbon chain into the phenolic resin. The flexible characteristics of the aliphatic long carbon chain are entangled with the phenolic chain segments to form a synergistic toughening crosslink. After curing, the stability between the interface of the carbon fiber felt and the interface of the carbon-carbon composite sheet is improved, thereby strengthening the bonding force and increasing the adhesion life, thereby increasing the service life of the thermal insulation hard felt at ultra-high temperatures.

[0012] Optionally, the long-chain acid ester is selected from one or both of butyl dodecanoate and butyl myristate.

[0013] By adopting the above technical scheme and selecting the above two long-chain acid esters, the flexible winding effect of the long carbon chain can be brought into play, and the polarity matching of the molecular structure can be affected by the excessive length of the fatty carbon chain. Therefore, the selection of butyl dodecanoate and butyl tetradecanoate can effectively improve the stability of the thermal insulation hard felt.

[0014] Optionally, the aminosilane coupling agent is one or both of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0015] Optionally, the molar ratio of the long-chain acid ester to the aminosilane coupling agent is 1:1.

[0016] Optionally, the dispersant is selected from one or more of diethylene glycol butyl ether, propylene glycol methyl ether and triethylene glycol monobutyl ether.

[0017] By adopting the above technical solution, the types of the above dispersants can make the insoluble carbon powder, graphite powder and silicon carbide uniformly dispersed in the solvent, so as to play the filling role of carbon powder, graphite powder and silicon carbide.

[0018] Optionally, the carbonization aid is cellulose and / or cellulose derivatives.

[0019] By adopting the above technical solution, cellulose can promote the high-temperature carbonization process, thereby promoting the formation of a dense cross-linked network structure and further improving the stability of the thermal insulation hard felt.

[0020] Optionally, the carbon fiber felt body is made of carbon fiber soft felt coated with silicon-modified phenolic resin, and the mass ratio of the carbon fiber soft felt to the silicon-modified phenolic resin is 1:(1-1.5).

[0021] By adopting the above technical solution, the carbon fiber soft felt is coated with silicon-modified phenolic resin, so that the structure of the carbon fiber felt body can also withstand high temperatures, thereby improving the overall high-temperature stability of the thermal insulation hard felt.

[0022] Optionally, the carbon powder is amorphous and has no long-range ordered crystal structure. The graphite powder is a layered structure and presents a hexagonal crystal system.

[0023] Optionally, the solvent is methanol or ethanol.

[0024] In the second aspect, the present application provides a method for preparing a composite thermal insulation hard felt using the following technical solution: The solvent, furan resin and silicon-modified phenolic resin are mixed and stirred, carbon powder, graphite powder and silicon carbide are added and mixed and stirred, and then a dispersant and a carbonization aid are added and mixed and stirred to prepare a binder; Applying a binder to the surface of the carbon-carbon composite sheet, attaching the carbon fiber soft felt to the carbon-carbon composite sheet, and baking to obtain a preliminary composite hard felt; The preliminary composite hard felt is placed in an environment of not less than 2000° C. for vacuum high-temperature carbonization treatment to obtain a composite thermal insulation hard felt.

[0025] By adopting the above technical solution, carbon powder, graphite powder and silicon carbide are added after the resin and solvent are mixed. Carbon powder is the main filler, which can increase the residual carbon rate of the binder and strengthen the bonding force of the binder at high temperature. Graphite powder and silicon carbide can also play a filling role, and graphite powder can increase the lubricity of the binder, so that the binder can be better coated on the surface of the carbon-carbon composite sheet. The high temperature resistance of silicon carbide itself can enhance the high temperature stability of the binder. Due to the insoluble characteristics of carbon powder, graphite powder and silicon carbide, a dispersant is added in the subsequent step to improve the dispersibility of carbon powder, graphite powder and silicon carbide.

[0026] The carbon fiber soft felt and the carbon-carbon composite sheet are attached and baked to achieve preliminary shaping. The preliminary composite hard felt after the preliminary shaping is carbonized at high temperature to form a carbon fiber felt body while completing the close combination of the carbon fiber felt body and the carbon-carbon composite sheet, thereby resisting the erosion of high-temperature steam and extending the service life of the thermal insulation hard felt.

[0027] Optionally, under the protection of an inert gas, the aminosilane coupling agent, the long-chain acid ester and the organic solvent are heated to 80-90° C. while being mixed for reaction, and after the reaction is completed, the solvent is removed by negative pressure distillation to obtain a long-chain silane coupling agent; Mixing a long-chain silane coupling agent and an ethanol solution, adjusting the pH to a weakly alkaline state, and hydrolyzing the mixture to obtain a hydrolyzed mixed solution; Phenol and part of the catalyst solution are mixed, heated to 60-70°C and reacted for 20-40 minutes, then part of the formaldehyde is added, heated to 85-90°C and reacted for 1-1.5 hours, then the remaining catalyst solution and the remaining formaldehyde are added, and then the hydrolysis mixture is added dropwise to the reaction solution, and the reaction is continued for 1-2 hours, and then the pH is adjusted to neutral, and vacuum dehydration is performed to obtain a silicon-modified phenolic resin.

[0028] By adopting the above technical scheme, the ester group of the long-chain acid ester reacts and bonds with the amino group in the aminosilane coupling agent to form a long-chain silane coupling agent, and the long-chain silane coupling agent is grafted during the synthesis process of the phenolic resin to achieve silicon modification of the phenolic resin and improve the high-temperature stability of the phenolic resin.

[0029] Optionally, the organic solvent is a high boiling point alcohol, preferably n-butanol.

[0030] Optionally, the molar ratio of formaldehyde to phenol is 1:(1.2-1.4).

[0031] Optionally, the mass ratio of the long-chain silane coupling agent to phenol is (0.2-0.25):1.

[0032] Optionally, the catalyst solution is a NaOH solution, wherein the molar ratio of NaOH to phenol is (0.02-0.03):1.

[0033] Optionally, the method for preparing the carbon-carbon composite sheet comprises the following steps: The chopped carbon fiber is air-laid and then needle-punched to form a carbon fiber mesh, which is then placed in a mold. Furan resin is added to the mold, and the mold is pressed and pre-cured at 170-180°C for 2-3 hours. The mold is then demolded and placed in a vacuum furnace for carbonization at 2000-2200°C for 4-5 hours to obtain a carbon-carbon composite sheet.

[0034] In summary, this application has the following beneficial effects: 1. The present application provides a carbon-carbon composite sheet on the basis of a carbon fiber felt body. The carbon-carbon composite sheet is a thin sheet formed of a carbon-carbon composite material. Since carbon atoms have a strong affinity with each other, the carbon-carbon composite sheet has good stability, can resist the erosion of high-temperature steam in the silicon carbide thermal field, and protect the carbon fiber felt body. The binder enables the carbon-carbon composite sheet to have a high bond with the carbon fiber felt body and is not easy to separate under high temperature conditions. Silicon-modified phenolic resin introduces silicone to produce good high temperature resistance, so that the phenolic resin and furan resin form a stable cross-linked network. Graphite powder, carbon powder and silicon carbide are doped in the cross-linked network to play a role of filling and lubricating dispersion, strengthen the bonding force of the binder on the carbon-carbon composite sheet and the carbon fiber felt body, and further improve the overall structural stability of the thermal insulation hard felt, so that the thermal insulation hard felt can still be stable for a long time under ultra-high temperatures, and improve the overall service life of the thermal insulation hard felt.

[0035] 2. The silicon-modified phenolic resin of the present application is a phenolic resin modified by a long-chain silane coupling agent. The long-chain silane coupling agent introduces silicone into the phenolic resin while also introducing aliphatic long carbon chains into the phenolic resin. The flexibility of the aliphatic long carbon chains is utilized to entangle with the phenolic chain segments to form synergistic toughening crosslinks. After curing, the stability between the interface of the carbon fiber felt and the interface of the carbon-carbon composite sheet is improved, thereby strengthening the bonding force, increasing the adhesion life, and further increasing the service life of the thermal insulation hard felt at ultra-high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a cross-sectional structural diagram of the composite thermal insulation hard felt of Example 1 of the present application.

[0037] Description of reference numerals: 1. Carbon fiber felt body; 2. Carbon-carbon composite sheet. DETAILED DESCRIPTION

[0038] The following is combined with Figure 1 This application is described in further detail.

[0039] Preparation Example 1 The preparation method of silicon-modified phenolic resin comprises the following steps: Weigh 331.5 g of an aminosilane coupling agent, 384 g of a long-chain acid ester, and 300 g of an organic solvent, wherein the aminosilane coupling agent is specifically 3-aminopropyltriethoxysilane, the long-chain acid ester is specifically butyl dodecanoate, and the organic solvent is specifically n-butanol.

[0040] The aminosilane coupling agent, the long-chain acid ester and the organic solvent are placed in a reaction container and mixed, and nitrogen is introduced for protection, and then heated to 80° C. for reflux reaction for 4 hours. After the reaction is completed, the solvent is removed by negative pressure distillation to obtain a long-chain silane coupling agent.

[0041] Weigh 403g of long-chain silane coupling agent, 400g of ethanol solution, 376g of phenol, 283g of formaldehyde solution, and 320g of catalyst solution, wherein the concentration of the ethanol solution is 90wt%; the concentration of the formaldehyde solution is 35wt%; and the catalyst solution is specifically a 1wt% NaOH solution.

[0042] The long-chain silane coupling agent and the ethanol solution were placed in a reaction container and mixed, and NaOH was added to adjust the pH to 8.5, and hydrolyzed at room temperature for 3 hours to obtain a hydrolyzed mixed solution.

[0043] Phenol and a catalyst solution accounting for 50 wt% of the total catalyst solution are placed in a reaction container and mixed, heated to 60°C for reaction for 40 minutes, then a formaldehyde solution accounting for 40 wt% of the total formaldehyde solution is added, heated to 85°C for reaction for 1 hour, then the remaining catalyst solution and the remaining formaldehyde solution are added, then the hydrolysis mixture is added dropwise to the reaction solution, the reaction is continued for 1 hour, acetic acid is added to adjust the pH to 7, and water and ethanol are removed by vacuum to obtain a silicon-modified phenolic resin.

[0044] Preparation Example 2 The preparation method of silicon-modified phenolic resin comprises the following steps: Weigh 331.5 g of an aminosilane coupling agent, 384 g of a long-chain acid ester, and 300 g of an organic solvent, wherein the aminosilane coupling agent is specifically 3-aminopropyltriethoxysilane, the long-chain acid ester is specifically butyl dodecanoate, and the organic solvent is specifically n-butanol.

[0045] The aminosilane coupling agent, the long-chain acid ester and the organic solvent are placed in a reaction container and mixed, and nitrogen is introduced for protection, and then heated to 80° C. for reflux reaction for 4 hours. After the reaction is completed, the solvent is removed by negative pressure distillation to obtain a long-chain silane coupling agent.

[0046] Weigh 403g of long-chain silane coupling agent, 400g of ethanol solution, 470g of phenol, 306g of formaldehyde solution, and 600g of catalyst solution, wherein the concentration of the ethanol solution is 90wt%; the concentration of the formaldehyde solution is 35wt%; and the catalyst solution is specifically 1wt% NaOH solution.

[0047] The long-chain silane coupling agent and the ethanol solution were placed in a reaction container and mixed, and NaOH was added to adjust the pH to 8.5, and hydrolyzed at room temperature for 3 hours to obtain a hydrolyzed mixed solution.

[0048] Phenol and a catalyst solution accounting for 50 wt% of the total catalyst solution are placed in a reaction container and mixed, heated to 70°C for reaction for 20 minutes, then a formaldehyde solution accounting for 40 wt% of the total formaldehyde solution is added, heated to 90°C for reaction for 1.5 hours, then the remaining catalyst solution and the remaining formaldehyde solution are added, then the hydrolysis mixture is added dropwise to the reaction solution, the reaction is continued for 2 hours, acetic acid is added to adjust the pH to 7, and water and ethanol are removed by vacuum to obtain a silicon-modified phenolic resin.

[0049] Preparation Example 3 Preparation method of silicon-modified phenolic resin The difference between this preparation example and preparation example 1 is that the long-chain acid ester is specifically butyl octadecanoate.

[0050] Preparation Example 4 The preparation method of silicon-modified phenolic resin comprises the following steps: Weigh 221g of aminosilane coupling agent, 200g of ethanol solution, 376g of phenol, 283g of formaldehyde solution, and 320g of catalyst solution. The aminosilane coupling agent is specifically 3-aminopropyltriethoxysilane; the concentration of the ethanol solution is 90wt%; the concentration of the formaldehyde solution is 35wt%; and the catalyst solution is specifically 1wt% NaOH solution.

[0051] The aminosilane coupling agent and the ethanol solution were placed in a reaction container and mixed, and NaOH was added to adjust the pH to 8.5, and hydrolyzed at room temperature for 3 hours to obtain a hydrolyzed mixed solution.

[0052] Phenol and a catalyst solution accounting for 50 wt% of the total catalyst solution are placed in a reaction container and mixed, heated to 60°C for reaction for 40 minutes, then a formaldehyde solution accounting for 40 wt% of the total formaldehyde solution is added, heated to 85°C for reaction for 1 hour, then the remaining catalyst solution and the remaining formaldehyde solution are added, then the hydrolysis mixture is added dropwise to the reaction solution, the reaction is continued for 1 hour, acetic acid is added to adjust the pH to 7, and water and ethanol are removed by vacuum to obtain a silicon-modified phenolic resin.

[0053] Blank Preparation Example The preparation method of phenolic resin comprises the following steps: Weigh 376g of phenol, 283g of formaldehyde solution, and 320g of catalyst solution, wherein the concentration of the ethanol solution is 90wt%, the concentration of the formaldehyde solution is 35wt%, and the catalyst solution is specifically a 1wt% NaOH solution.

[0054] Phenol and a catalyst solution accounting for 50 wt% of the total catalyst solution are placed in a reaction container and mixed, heated to 60°C for reaction for 40 minutes, then a formaldehyde solution accounting for 40 wt% of the total formaldehyde solution is added, heated to 85°C for reaction for 1 hour, then the remaining catalyst solution and the remaining formaldehyde solution are added, the reaction is continued for 1 hour, acetic acid is added to adjust the pH to 7, and water and ethanol are removed by vacuum to obtain a phenolic resin.

[0055] Preparatory Example 1 The method for preparing a carbon-carbon composite sheet comprises the following steps: The chopped carbon fiber is air-laid and needle-punched to form a carbon fiber mesh, and then the carbon fiber mesh is placed in a mold. Resin is added to the mold. The mass ratio of the carbon fiber mesh to the resin is 1:1.5. The resin is specifically F14 furan resin. After the mold is pressed, it is pre-cured at 170°C for 3h, then demolded, and placed in a vacuum furnace for carbonization at 2000°C for 5h. Finally, a carbon-carbon composite sheet is prepared. The thickness of the carbon-carbon composite sheet is 3±1mm and the density is 1.5g / cm 3 .

[0056] Preparatory Example 2 The method for preparing a carbon-carbon composite sheet comprises the following steps: The chopped carbon fiber was air-laid and needle-punched to form a carbon fiber mesh, and then the carbon fiber mesh was placed in a mold. Resin was added to the mold. The mass ratio of the carbon fiber mesh to the resin was 1:1.7. The resin was specifically F14 furan resin. After the mold was pressed, it was pre-cured at 180°C for 2h, then demolded, and placed in a vacuum furnace for carbonization at 2100°C for 4h. Finally, a carbon-carbon composite sheet was prepared. The thickness of the carbon-carbon composite sheet was 3±1mm and the density was 1.8g / cm 3 .

[0057] Example 1 like Figure 1 As shown, the composite thermal insulation hard felt includes a carbon fiber felt body 1 and a carbon-carbon composite sheet 2. The carbon-carbon composite sheet 2 is attached to the surface of the carbon fiber felt body 1 by an adhesive, and the carbon-carbon composite sheet 2 is located on the side of the carbon fiber felt body 1 facing the heat field.

[0058] The preparation method of the composite thermal insulation hard felt comprises the following steps: The carbon fiber soft felt is made by air-laying short carbon fibers and then needle-punching them. The cut carbon fiber soft felt is coated with the silicon-modified phenolic resin prepared in Preparation Example 1. The mass ratio of the carbon fiber soft felt to the silicon-modified phenolic resin is 1:1, and a carbon fiber felt body is obtained.

[0059] Weigh 2kg of furan resin, 0.5kg of silicon-modified phenolic resin, 0.5kg of graphite powder, 1.5kg of carbon powder, 0.1kg of silicon carbide powder, 0.2kg of dispersant, 0.1kg of carbonization aid, and 5.1kg of solvent. The furan resin is specifically Shiyi F14 furan resin; the silicon-modified phenolic resin is prepared in Preparation Example 1; the dispersant is specifically diethylene glycol butyl ether; the carbonization aid is specifically cellulose; and the solvent is specifically 95wt% ethanol solution.

[0060] First, the solvent, furan resin and silicon-modified phenolic resin are placed in a stirring kettle and mixed for 5 minutes, then carbon powder, graphite powder and silicon carbide are added and mixed for 3 minutes, and then a dispersant and a carbonization aid are added and mixed for 1 hour to prepare a binder.

[0061] The binder was applied to the surface of the carbon-carbon composite sheet prepared in Preparatory Example 1, with a coating amount of 1.1 kg / m 2 , attach the carbon fiber soft felt to the carbon-carbon composite sheet, bake it at 160°C for 2 hours, and obtain a preliminary composite hard felt.

[0062] The preliminary composite hard felt was placed in a vacuum high-temperature furnace, first heated to 500°C for 7 hours, then heated to 1000°C for 4 hours, then heated to 2000°C for 4 hours, and maintained at 2000°C for 5 hours to achieve carbonization treatment to obtain a composite thermal insulation hard felt.

[0063] Example 2 The difference between this embodiment and embodiment 1 lies in the different preparation methods of the composite thermal insulation hard felt, specifically, the different amounts of raw materials used for the binder and the different carbon-carbon composite sheets.

[0064] 2.5kg furan resin, 0.8kg silicon-modified phenolic resin, 0.8kg graphite powder, 2kg carbon powder, 0.2kg silicon carbide powder, 0.3kg dispersant, 0.2kg carbonization aid, 3.2kg solvent. The furan resin is specifically Shiyi F14 furan resin; the silicon-modified phenolic resin is prepared by Preparation Example 2; the dispersant is specifically diethylene glycol butyl ether; the carbonization aid is specifically cellulose; and the solvent is specifically 95wt% ethanol solution.

[0065] The mass ratio of the carbon fiber soft felt to the silicon-modified phenolic resin is 1:1.5.

[0066] The carbon-carbon composite sheet was prepared according to Preparation Example 2.

[0067] Example 3 The difference between this embodiment and embodiment 1 lies in the different preparation methods of the composite thermal insulation hard felt, specifically, the different amounts of raw materials used for the binder.

[0068] 2.2kg furan resin, 0.6kg silicon-modified phenolic resin, 0.7kg graphite powder, 1.6kg carbon powder, 0.15kg silicon carbide powder, 0.24kg dispersant, 0.17kg carbonization aid, 4.34kg solvent. The furan resin is specifically Shiyi F14 furan resin; the silicon-modified phenolic resin is prepared by Preparation Example 1; the dispersant is specifically diethylene glycol butyl ether; the carbonization aid is specifically cellulose; and the solvent is specifically 95wt% ethanol solution.

[0069] Example 4 The difference between this embodiment and embodiment 1 lies in the different preparation methods of the composite thermal insulation hard felt, specifically, the silicon-modified phenolic resin is prepared by Preparation Example 3.

[0070] Example 5 The difference between this embodiment and embodiment 1 lies in the different preparation methods of the composite thermal insulation hard felt. Specifically, the silicon-modified phenolic resin is prepared by Preparation Example 4.

[0071] Comparative Example 1 Preparation method of thermal insulation hard felt The carbon fiber soft felt is made by air-forming short carbon fibers into a web and then needle-punching them. The cut carbon fiber soft felt is coated with the phenolic resin prepared in the blank preparation example, the mass ratio of the carbon fiber soft felt to the phenolic resin is 1:1, and then baked at a temperature of 160°C for 2 hours to obtain a preliminary hard felt.

[0072] The preliminary hard felt was placed in a vacuum high-temperature furnace, first heated to 500°C for 7 hours, then heated to 1000°C for 4 hours, then heated to 2000°C for 4 hours, and maintained at 2000°C for 5 hours to achieve carbonization treatment and obtain thermal insulation hard felt.

[0073] Comparative Example 2 The difference between this comparative example and Example 1 lies in the different preparation methods of the composite thermal insulation hard felt, specifically, the different raw materials of the binder and the different carbon fiber felt bodies.

[0074] The preparation method of the composite thermal insulation hard felt comprises the following steps: 2 kg of the silicon-modified phenolic resin obtained in Preparation Example 1, 0.5 kg of graphite powder, 1.5 kg of carbon powder, 0.1 kg of silicon carbide powder, and 0.2 kg of a dispersant were mixed and stirred for 0.5 h to obtain a coating agent.

[0075] The carbon fiber soft felt is formed by air-forming short carbon fibers into a web and then needle-punching them. The cut carbon fiber soft felt is coated with a coating agent, and the mass ratio of the carbon fiber soft felt to the coating agent is 1:1, so as to obtain a carbon fiber felt body.

[0076] Weigh 2kg of furan resin, 0.5kg of silicon-modified phenolic resin, 0.1kg of carbonization aid, and 5.1kg of solvent. The furan resin is specifically Shiyi F14 furan resin; the silicon-modified phenolic resin is prepared in Preparation Example 1; the dispersant is specifically diethylene glycol butyl ether; the carbonization aid is specifically cellulose; and the solvent is specifically 95wt% ethanol solution.

[0077] Firstly, the solvent, furan resin and silicon-modified phenolic resin were placed in a stirring kettle and mixed and stirred for 5 minutes, and then a carbonization aid was added and mixed and stirred for 0.5 hours to prepare a binder.

[0078] The binder was applied to the surface of the carbon-carbon composite sheet prepared in Preparation Example 1, with a coating amount of 1.1 kg / m 2 , attach the carbon fiber soft felt to the carbon-carbon composite sheet, bake it at 160°C for 2 hours, and obtain a preliminary composite hard felt.

[0079] The preliminary composite hard felt was placed in a vacuum high-temperature furnace, first heated to 500°C for 7 hours, then heated to 1000°C for 4 hours, then heated to 2000°C for 4 hours, and maintained at 2000°C for 5 hours to achieve carbonization treatment to obtain a composite thermal insulation hard felt.

[0080] Comparative Example 3 The difference between this comparative example and Example 1 lies in the different preparation methods of the composite thermal insulation hard felt, specifically, the silicon-modified phenolic resin is replaced with an equal amount of phenolic resin prepared in the blank preparation example.

[0081] Performance Testing Thermal insulation test: The finished products obtained in Examples 1-5 and Comparative Examples 1-3 were cut into test specimens, and the thermal conductivity was tested at 1500°C with reference to GB / T22588-2008 "Flash method for measuring thermal diffusion coefficient or thermal conductivity". The results are shown in Table 1.

[0082] Thermal insulation continuity test: The finished products obtained in Examples 1-5 and Comparative Examples 1-3 were placed in the same silicon carbide growth furnace and used for three months. During this period, the daily maximum operating temperature of the silicon carbide growth furnace reached 2400°C. After three months, the finished products were taken out and cut into test specimens. Finally, the thermal conductivity coefficient was tested. The results are shown in Table 1.

[0083] Structural stability: In the above insulation continuity test, after taking out the finished product three months later and cutting it into test specimens, observe whether the finished product has any powder falling off during the cutting process, and press the finished product to observe whether it is fragile.

[0084] Table 1 It can be seen from the test results in Table 1 that after three months of use, the composite thermal insulation hard felt of Examples 1-3 still maintains a low thermal conductivity, that is, has good thermal insulation continuity, and has structural characteristics of no obvious powdering and not being easy to break, indicating that the composite thermal insulation hard felt is used under continuous high temperature in the silicon carbide thermal field, can resist the erosion of environmental high temperature steam, and has good durability.

[0085] The thermal conductivity of the finished product of Comparative Example 1 increases significantly after three months of use, while the thermal insulation decreases and the structural stability is poor. Compared with Example 1, it can be explained that the carbon-carbon composite sheet can play a barrier and protective role on the carbon fiber felt body, thereby improving the overall structural stability of the composite thermal insulation hard felt, reducing the structural damage of the composite thermal insulation hard felt due to high-temperature steam erosion, and maintaining good thermal insulation.

[0086] The finished product of Comparative Example 2 also has reduced thermal insulation and poor structural stability after three months of use. Compared with Example 1, it can be explained that the binder in which graphite powder, carbon powder and silicon carbide powder are filled between the carbon fiber felt body and the carbon-carbon composite sheet can effectively enhance the bonding force between the carbon fiber felt body and the carbon-carbon composite sheet, and has a certain high temperature resistance effect, further reducing the erosion of high temperature steam on the internal structure, thereby improving the thermal insulation and structural stability of the composite thermal insulation hard felt.

[0087] The finished product of Comparative Example 3 also has reduced thermal insulation and poor structural stability after three months of use. Compared with Example 1, it can be shown that silicon-modified phenolic resin can improve bonding ability and high temperature resistance than ordinary phenolic resin, thereby improving the thermal insulation and stability of the composite thermal insulation felt.

[0088] The thermal insulation of the finished products of Example 4 and Example 5 is slightly reduced after three months of use, but the thermal conductivity is still below 0.40w / km, which indicates that the addition of long-chain acid esters can improve the high temperature resistance of the adhesive. In addition, the selection of the length of the long-chain acid ester segment will also affect the thermal insulation.

[0089] In addition, the finished products obtained in Example 1 and Comparative Example 1 were used as insulation materials for two silicon carbide growth furnaces respectively. The two silicon carbide growth furnaces maintained the same frequency of use and produced the same batch of products within three months. After three months of use, the energy consumption of the two silicon carbide growth furnaces was counted. The final results showed that the silicon carbide growth furnace using the finished product of Example 1 as the insulation material saved 15.3% in energy consumption compared with the silicon carbide growth furnace using the finished product of Comparative Example 1 as the insulation material, indicating that the finished product of Example 1 can resist the erosion of high-temperature gas in the thermal field, maintain the structural stability of the composite insulation hard felt, thereby maintaining the thermal insulation performance, reducing the dissipation of heat energy to the outside, and saving energy consumption.

[0090] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A composite thermal insulation hard felt, characterized in that: It comprises a carbon fiber felt body and a carbon-carbon composite sheet, wherein the carbon-carbon composite sheet is attached to the surface of the carbon fiber felt body by an adhesive, and the adhesive is made of the following components in percentage by weight: Furan resin 20~25%; Silicon modified phenolic resin 5~8%; Graphite powder 5~8%; Carbon powder 15~20%; Silicon carbide powder 1~2%; Dispersant 2~3%; Carbonization aid 1~2%; The balance is solvent.

2. The composite thermal insulation hard felt according to claim 1, characterized in that: The carbon-carbon composite sheet is made of carbon fiber solidified by resin, the mass ratio of carbon fiber to resin is 1:(1.5-1.7), the thickness is 3±1mm, and the density is 1.5-1.8g / cm 3 .

3. The composite thermal insulation hard felt according to claim 1, characterized in that: The silicon-modified phenolic resin is a phenolic resin modified by a long-chain silane coupling agent, wherein the long-chain silane coupling agent is formed by reacting a long-chain acid ester with an aminosilane coupling agent, and the long-chain silane coupling agent is added during the synthesis of the phenolic resin to obtain the long-chain silane coupling agent modified phenolic resin.

4. The composite thermal insulation hard felt according to claim 3, characterized in that: The long-chain acid ester is selected from one or both of butyl dodecanoate and butyl myristate.

5. The composite thermal insulation hard felt according to claim 1, characterized in that: The dispersant is selected from one or more of diethylene glycol butyl ether, propylene glycol methyl ether and triethylene glycol monobutyl ether.

6. The composite thermal insulation hard felt according to claim 1, characterized in that: The carbonization aid is cellulose and / or cellulose derivatives.

7. The composite thermal insulation hard felt according to claim 1, characterized in that: The carbon fiber felt body is made of carbon fiber soft felt coated with silicon-modified phenolic resin, and the mass ratio of the carbon fiber soft felt to the silicon-modified phenolic resin is 1:(1-1.5).

8. A method for preparing a composite thermal insulation hard felt according to any one of claims 1 to 7, characterized in that: The following steps are involved: The solvent, furan resin and silicon-modified phenolic resin are mixed and stirred, carbon powder, graphite powder and silicon carbide are added and mixed and stirred, and then a dispersant and a carbonization aid are added and mixed and stirred to prepare a binder; Applying a binder to the surface of the carbon-carbon composite sheet, attaching the carbon fiber soft felt to the carbon-carbon composite sheet, and baking to obtain a preliminary composite hard felt; The preliminary composite hard felt is placed in an environment of not less than 2000° C. for vacuum high-temperature carbonization treatment to obtain a composite thermal insulation hard felt.

9. The method for preparing a composite thermal insulation hard felt according to claim 8, characterized in that: The preparation method of the silicon-modified phenolic resin comprises the following steps: Under the protection of inert gas, the aminosilane coupling agent, the long-chain acid ester and the organic solvent are mixed and heated to 80-90° C. for reaction, and after the reaction is completed, the solvent is removed by negative pressure distillation to obtain a long-chain silane coupling agent; The long-chain silane coupling agent and the ethanol solution are mixed, the pH is adjusted to be weakly alkaline, and hydrolyzed to obtain a hydrolyzed mixed solution; Phenol and part of the catalyst solution are mixed, heated to 60-70°C and reacted for 20-40 minutes, and then part of the formaldehyde is added, heated to 85-90°C and reacted for 1-1.5 hours, and then the remaining catalyst solution and the remaining formaldehyde are added, and then the hydrolysis mixture is added dropwise to the reaction solution, and the reaction is continued for 1-2 hours, and then the pH is adjusted to neutral, and vacuum dehydration is performed to obtain a silicon-modified phenolic resin.

10. The method for preparing a composite thermal insulation hard felt according to claim 8, characterized in that: The method for preparing the carbon-carbon composite sheet comprises the following steps: The chopped carbon fiber is air-laid and then needle-punched to form a carbon fiber mesh. The carbon fiber mesh is then placed in a mold, resin is added to the mold, and the mold is pressed together and pre-cured at 170-180°C for 2-3 hours. The mold is then demolded and placed in a vacuum furnace for carbonization at 2000-2100°C for 4-5 hours to obtain a carbon-carbon composite sheet.

Citation Information

Patent Citations

  • Carbon fiber felt lamination sheet and preparation method thereof

    CN106433019A

  • Organic silicon modified phenolic resin and preparation method thereof

    CN106496473A

  • Composite hard felt and preparation method thereof

    CN116373403A

  • Hard felt coating and preparation method thereof as well as carbon fiber hard felt and preparation method thereof

    CN116837642A

  • Preparation method of carbon-carbon composite material

    CN117534499A